Economies of scale and technological development in securities depository and settlement systems - Heiko Schmiedel; Markku Malkamäki; Juha Tarkka (Bank of Finland, 2002)
The paper investigates the existence and extent of economies of scale in depository and settlement systems.Evidence from 16 settlement institutions across different regions for the years 1993-2000 indicates the existence of significant economies of scale.The degree of such economies, however, differs by size of settlement institution and region.While smaller settlement service providers reveal high potential of economies of scale, larger institutions show an increasing trend of cost effectiveness. Clearing and settlement systems in countries in Europe and Asia report substantially larger economies of scale than those of the US system.European cross-border settlement seems to be more cost intensive than that on a domestic level, reflecting chiefly complexities of EU international securities settlement and differences in the scope of international settlement services providers.The evidence also reveals that investments in implementing new systems and upgrades of settlement technology continuously improved cost effectiveness over the sample period.
URN:NBN:fi:bof-20140807243
Keywords: G20; F36; L22; O33; 330; securities settlement; economies of scale; technological progress